Mitochondrial modifying nutrients in treating chronic fatigue syndrome: A 16-week open-label pilot study. Issue 3 (December 2017) - Menon, Ranjit; Cribb, Lachlan; Murphy, Jenifer; Ashton, Melanie M.; Oliver, Georgina; Dowling, Nathan; Turner, Alyna; Dean, Olivia; Berk, Michael; Ng, Chee H.; Sarris, Jerome
Abstract: Introduction: Recent evidence suggests that mitochondrial dysfunction may play a role in the pathophysiology of chronic fatigue syndrome (CFS). We undertook a pilot investigation of a combination of nutraceutical nutrient compounds which are involved in mitochondrial function and energy generation, to assess their efficacy in improving symptoms of CFS. An open-label design was employed as CFS is largely treatment-resistant with limited placebo-response. Methods: A 16-week open-label trial of a nutraceutical combination (primary nutrients: Coenzyme Q10, Alpha lipoic acid, Acetyl-l -carnitine, N -acetyl cysteine, B Vitamins, in addition to co-factors) was undertaken in ten patients with CFS. Fatigue symptoms, mood and general health were assessed at each 4-week time point over 16 weeks. Of the ten patients (7 female, 3 male) with a mean age of 36.3, eight completed the trial. Results: Linear mixed model analysis demonstrated a significant improvement in fatigue symptoms across treatment period on the Chalder Fatigue Scale ( p <  0.001). Specific improvements were found in tiredness, weakness, feeling sleepy or drowsy, as well as in sleep, and clinician-reported symptom-improvement. No benefit was observed in mood or other functional domains. No serious adverse events were noted. Conclusion: These preliminary findings suggest that a combination nutraceutical compound of mitochondrial agents may improve CFS symptoms. Further investigation is warranted in a larger double-blind RCT.